Analisis Legal Standing Pemohon: Studi Putusan MK No. 133/PUU-XXIII/2025 - Wulandari, Amalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the Constitutional Court's considerations in determining the legal standing of the petitioners in Constitutional Court Decision Number 133/PUU-XXIII/2025. Legal standing is a key requirement that determines whether a petition for judicial review of a law can be accepted by the Constitutional Court. This study uses a normative juridical method with a legislative and case-based approach to the decision. The results of the study show that the Court found that the petitioners failed to convince the Court that there was actual or potential damage to their constitutional rights as a result of the implementation of the article being challenged. Therefore, the petition was deemed inadmissible due to the incompleteness of the legal standing requirement as stipulated in Article 51 paragraph (1) of Law Number 24 of 2003. This decision emphasizes the importance of proving the causal relationship between constitutional harm and the norm being challenged in order to maintain the integrity of constitutional justice in Indonesia